STUDI PENGGUNAAN OBAT DIARE PADA ANAK PASIEN RAWAT INAP DI RSUD ANDI DJEMMA MASAMBA KABUPATEN LUWU UTARA PERIODE JANUARI-DESEMBER 2014 - Santi, Irma; Herman, Hendra; Aninditia, Dian Dwi (Fakultas Farmasi UMI, 2017)
Diarrhea is generally caused by the bacteria contamined in food and drink. If the bacteria are not the right treatment, it can be fatal and cause death. This research aimed to present the drug use on the diarrhea patient of hospitalized children ar RSUD Andi Djemma Masamba North Luwu district. This research used descriptive methodÂ by collecting data retrospectively. The data were collected by searching the treatmentÂ records given by doctors to diarrhea patient of hospitalized children. The data obtained included patient medical record number, sex, age, body temperature, therapy (drug name, dose, frequency, route of administration) and length of stay.Â The result showed that the diarrhea drug use on children included antibiotic drugs(cotrimoxazole 4,3%, amoxicillin 2,9%, gentamicin 4,3%, cefotaxime 1.4%) antimicrobial (metronidazole 14,5%) zinc supplements 30,4%,probiotics 2,9%, antipyretics (paracetamol 34,8%) antiemetic (methoclopramide 1,5%) and antidispepsia (omeprazole 2,9%).